Hemolytic Uremic Syndrome Associated with Pneumococcal Pneumonia. A Case Report - Ariel Efrén Uriarte Méndez; Andrés Prieto Apesteguía; Jesús Vila Díaz; Jorge Luis Capote Padrón; Kendrie Villavicencio Cardoso; Alnilam Fernández González (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2013)
Hemolytic uremic syndrome is a condition characterized by hemolytic microangiopathic anemia, thrombocytopenia and acute renal failure. In its classic form it is associated with diarrhea and it has a good prognosis. When there is an invasive pneumococcal disease as underlying condition, it has a mortality rate of 25%, and half of the surviving cases develop end-stage renal disease (ESRD). We present the case of a 17-month-old child with hemolytic uremic syndrome secondary to pneumonia with empyema, who after being anuric and in intensive peritoneal dialysis for 10 days achieved normal renal function. His successful treatment, along with the fact that there are no similar cases published in our province, encouraged us to carry out this work.